Revenue Enhancement of Bakso Bakar King Alim Through Marketing Strategies - Widiyanti, Epa; Musthofa , M. Arif; kadarsih, Sri; Abidin, Zaenal; Kartika Devi, Erwina; Yatima, Khusnul; Fatimah, Siti (CV. Civiliza Publishing, 2025)
This study aims to analyze the marketing strategies implemented by the micro-enterprise Bakso Bakar King Alim, located in Muara Sabak Barat Subdistrict, Tanjung Jabung Timur Regency, Jambi Province, in its efforts to survive and grow amid local market competition. The research employs a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The findings indicate that the business applies a marketing mix strategy that encompasses product differentiation through grilling techniques and signature seasoning blends, pricing tailored to the local purchasing power, strategic location selection, and promotion that combines digital media such as WhatsApp with word-of-mouth communication. The novelty of this research lies in the integration of digital approaches with the strength of local community networks in expanding market reach and enhancing customer loyalty. The implications of this study may serve as a reference for other micro-enterprises in developing contextual, affordable, and sustainability-oriented marketing strategies, as well as for policymakers in designing MSME empowerment programs based on local potential